Perbedaan Jus Jambu Biji dan Tablet Fe Terhadap Peningkatan Kadar Haemoglobin Di Wilayah Kerja Puskesmas Cinere Tahun 2023 - Anggraeni, Ayu Kurnia (Bunda Edu-Midwifery Journal (BEMJ), 2023)
The objective in this research are 32 person third rimester pregnant women Research design using Quasi Experiment with The Nonrandomized Two Group Pretest and Postest Design. Data analysis Shapiro-Wilk test. The results of the study were obtained Hb levels before being given Guava Juice averaged equal to 10.45. Hb levels after being given guava juice: Average equal to 11.119. Hb levels before being given Fe tablets: Average equal to 10.294. Hb levels after being given Fe tablets: Average equal to 10,531. There is a difference in the increase in hemoglobin levels of pregnant women given guava juice with pregnant women given Fe tablets in the Cinere Public Health Center in 2023.